Analisis Faktor-Faktor yang Mempengaruhi Pertumbuhan Laba pada Perusahaan Kelapa Sawit PT Bungo Limbur/KBI di Muara Bungo - Uci Liati; Ahsan Putra Hafiz; Puteri Anggi Lubis (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to know the impact of CPO Prices and Production Costs on Profit Growth in Palm Oil Companies. This study uses a quantitative approach with primary data in the form of interviews, questionnaires and documentation. Sampling in this study used a sampling technique with a sample of 60 people. The method used in this study is multiple linear regression analysis using IBM SPSS as the application. The results of this study show that CPO prices do not have a significant effect on profit growth and operating costs have a significant effect on profit growth. For the results of simultaneous testing (F test), namely the price of CPO and production costs have a joint effect on the company's profit growth. The results of the determination coefficient (R2) show that CPO prices and production costs can explain profit growth of 49.5% while the rest is not studied in this study